Computer tablet-based health technology for strengthening maternal and child tracking in Bihar - Preeti Negandhi; Monika Chauhan; Ankan Mukherjee Das; Jyoti Sharma; Sutapa Neogi; Ghanashyam Sethy (Wolters Kluwer Medknow Publications, 2016)
Background: UNICEF along with the State Government of Bihar launched a computer tablet-based Mother and Child Tracking System (MCTS) in 2014, to capture real-time data online and to minimize the challenges faced with the conventional MCTS. Objective: The article reports the process of implementation of tablet-based MCTS in Bihar. Methods: In-depth interviews with medical officers, program managers, data managers, auxiliary nurse midwives (ANMs), and a monitoring and evaluation specialist were conducted in October 2015 to understand the process of implementation, challenges and possibility for sustainability, and scale-up of the innovation. Results: MCTS innovation was introduced initially in one Primary Health Centre each in Gaya and Purnia districts. The device, supported with Android MCTS software and connected to a dummy server, was given to ANMs. ANMs were trained in its application. The innovation allows real-time data entry, instant uploading, and generation of day-to-day work plans for easy tracking of beneficiaries for providing in-time health-care services. The nonlinking of the dummy server to the national MCTS portal has not lessened the burden of data entry operators, who continue to enter data into the national portal as before. Conclusion: The innovation has been successfully implemented to meet its objective of tracking the beneficiaries. The national database should be linked to the dummy server or visible impact. The model is sustainable if the challenges can be met. Mobile technology offers a tremendous opportunity to strengthen the capacity of frontline workers and clinicians and increase the quality, completeness, and timeliness of delivery of critical health services.